Knowledge Society (Docentes 2.0 Journal, 2019)
The notion of a knowledge society is an innovation of information and communications technologies, where the increase in information transfers modified in many ways the way in which they carry out many activities in modern society. It was first used by the business management philosopher Drucker, whose ideas were decisive in the creation of the modern Corporation, who had previously coined the term "knowledge worker" and is now considered the father of management as a discipline.
Keywords: Knowledge; Society